Características funcionais e relações energéticas de anuros arborícolas de um fragmento da Floresta Atlântica. - Maciel, Amanda Lipinski Fernandes (2018)
The Atlantic Forest presents only between 11% and 16% of forest remnants. As a result of the high degradation of this biome, amphibian populations have been declining considerably when faced with risks such as dehydration, predation and agrochemical contaminants. Although the various studies involve anurans energy expenditure, especially during breeding and hibernation, studies investigating and testing the energetic influence on species distribution are indispensable because they provide important information about the ecology of these organisms. For this, five arboreal species of open areas and four arboreal species with forest edges were sampled. The energetic content of these species was obtained and related to three of their functional characteristics, being: habitat type, size and diversity of antipredation mechanisms. From this, it was verified that: 1) open area species have more energy than forest edge species; 2) small species have more energy than medium and large species, and 3) species with a lower diversity of predation mechanisms have more energy than species with greater diversity. In addition, it was observed that size was the characteristic that best correlated with energy content (32.6%), followed by habitat (10%). The results indicate that the energy is strongly related to the reproduction in anurans, because species of open areas and small species, present in the majority, reproduction of the prolonged type, which demands a high energetic cost. In addition, because the energy content does not influence the distribution, but the anurans' specialization, the forest species end up becoming the most threatened, since species of open areas are better adapted to the degradation of the environment